Information and measuring system for geometric and motion parameters determination of industrial products by their video images - Yurii Podchashynskyi; Oksana Luhovykh; Anna Polianska; Volodymyr Nevmerzhytskyi (Технічна інженерія)
The article presents the information and measuring system for geometric and motion parameters determination of industrial products, for example, at a stone processing or machine-building enterprise. The proposed system allows automating measuring geometric parameters and quality control processes. The additional determination of product motion parameters allows compensation of dynamic errors in the video measurement data using software and algorithms. A distinctive feature of the proposed system for measuring geometric and motion parameters of objects is the use of non-contact measurements. Modern hardware and software such as a digital video camera and a computing module (personal computer); Python programming language with the OpenCV image processing library are used to build the system ensuring the measurement of geometric and motion parameters of products. The developed system is calibrated by the video images of objects with the given geometric dimensions before starting the operation. The information and measurement system operates in two measurement modes: manual and automatic. Measurements performed in the manual mode are more accurate than in the automatic mode. In addition, in the automatic mode, the software is supplied with video image normalisation and segmentation thresholding functions for more accurate measurements. A series of measurements have been made in manual and automatic modes. The nominal dimensions of the industrial product are 60.00 mm long and 75.00 mm wide, which is manufactured with a high accuracy class of these dimensions. The confidence intervals of the measurement results are as follows: for the manual mode: length is 59.68 ±0.46 mm, width is 74.78 ±0.54 mm; for the automatic mode: the length is 60.60 ±0.15 mm, the width is 74.95 ±0.13 mm. The proposed system provides an error of (0.13–0.54) mm when measuring the geometric parameters of industrial products, which may be sufficient for routine inspection, but insufficient for use in precision measurements. The main way to improve the accuracy to the requirements of precision measurements is to use a more advanced digital camera, software and algorithmic procedures for approximating and smoothing the contours of objects and motion parameters. Meanwhile, the main advantage of the developed system is the automation of the processes of measuring and controlling the industrial products geometric and motion parameters.